2010
DOI: 10.1193/1.3479930
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Motion Attenuation Model for Small-To-Moderate Shallow Crustal Earthquakes in California and Its Implications on Regionalization of Ground-Motion Prediction Models

Abstract: This paper presents the development of a ground-motion prediction model for small-to-moderate shallow crustal earthquakes (3M5.5, up to 200 km distance) using data from the California ShakeMap systems. Our goal is to provide an empirical model that can be confidently used in the investigation of ground-motion difference between California and other active tectonic regions (such as the Pacific Northwest and British Columbia, Canada) where the bulk of ground-motion data from shallow crustal earthquakes is in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 26 publications
5
100
2
1
Order By: Relevance
“…Bommer et al (2010) showed that GMPEs developed from pan-European datasets and ground-motion models derived from NGA-West1 GMPEs would yield similar ground-motion estimates for moderate-to-large magnitude earthquakes. These authors indicated that the regional differences in ground-motion estimates would be prominent towards smaller magnitude earthquakes, which is a parallel observation with the studies conducted in the other parts of the world (Chiou et al 2010;Atkinson and Morrison 2009). On the other hand, Scasserra et al (2009) emphasized that the use of NGA-West1 GMPEs may over predict the hazard in Italy at large distances because Italian data attenuate faster than the trends depicted in NGA-West1 GMPEs.…”
Section: Introductionsupporting
confidence: 65%
“…Bommer et al (2010) showed that GMPEs developed from pan-European datasets and ground-motion models derived from NGA-West1 GMPEs would yield similar ground-motion estimates for moderate-to-large magnitude earthquakes. These authors indicated that the regional differences in ground-motion estimates would be prominent towards smaller magnitude earthquakes, which is a parallel observation with the studies conducted in the other parts of the world (Chiou et al 2010;Atkinson and Morrison 2009). On the other hand, Scasserra et al (2009) emphasized that the use of NGA-West1 GMPEs may over predict the hazard in Italy at large distances because Italian data attenuate faster than the trends depicted in NGA-West1 GMPEs.…”
Section: Introductionsupporting
confidence: 65%
“…Median ground motions from southern Californian small earthquakes are up to two times those from northern events of the same size recorded at the same distance at a wide range of periods (Figure 3), which has been related by Chiou et al (2009) to variations in stress drop between the two areas. However, for larger earthquakes, which are the main focus of seismic hazard assessments the clear differences in ground motions between the two regions become negligible.…”
Section: Evidence From Weak-motion Datamentioning
confidence: 99%
“…Firstly, the importance of reducing 'pseudo-regional differences', such as general site variations between two areas, and, secondly, comparing weak motions in one region to weak motions in another. As shown by, for example, Bommer et al (2007) and Cotton et al (2008) ground motions from small earthquakes scale differently with respect to magnitude and source-to-site distance in small and large events and this effect must be accounted for when examining variations between ground motions in one region and those in another.…”
Section: Evidence From Weak-motion Datamentioning
confidence: 99%
See 2 more Smart Citations